First principles study on hydrogen storage in yttrium doped graphyne: Role of acetylene linkage in enhancing hydrogen storage. (21st June 2019) - Gangan, Abhijeet; Chakraborty, Brahmananda; Ramaniah, Lavanya M.; Banerjee, Srikumar
Abstract: Through Density Functional Theory Simulations we predict that a Ytrrium atom attached on graphyne surface can adsorb up to a maximum of 9 molecular hydrogens (H2 ), with a uniform binding energy of ∼0.3 eV/H2 and an average desorption temperature of around 400 K (ideal for fuel cell applications), leading to 10 wt% of hydrogen, substantially higher than the requirement by DoE. The higher hydrogen wt% in Y doped graphyne compared to Y doped Single Walled Carbon Nanotubes (SWNT) and graphene is due to the presence of sp hybridized C atoms (in the acetylene linkage) supplying additional in-plane p x -p y orbitals leading to π ( π* ) bonding (antibonding) states. Charge transfer from metal to carbon nanostructure results in a redistribution of s, p, d orbitals of the metal leading to a non - spin polarized ground state in Y doped graphyne, due to the presence of the acetylene linkage, whereas Y doped SWNT and graphene remain magnetic like the isolated metal atom. In the non-magnetic graphyne + Y system, the net charge transfer from Y to successive H2 molecules is less than in magnetic Y + graphene and Y + SWNT systems, enabling Y + graphyne to store a larger number of H2 molecules. Furthermore, our ab initio MD simulations show that the system is stable even at room temperature and there is no dissociation of H2 molecules, enabling the system to achieve 100% desorption. So Y doped graphyne is found to be a promising hydrogen storage device with high wt%, 100% recyclability and desirable desorption temperature. Highlights: Y attached on graphyne adsorb 9H2 with BE of ∼0.3 eV/H2 leading to 10 wt% of H2 . Almost uniform Desorption temperature of ∼400 K, ideal for fuel cell applications. Acetylene linkage make non-spin polarized ground state in Y doped graphyne. Magnetic character of the host can control hydrogen wt% and desorption temperature. System stable & can act as high capacity, 100% recyclable hydrogen storage device.